1994
DOI: 10.21273/jashs.119.4.824
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Incorporation of Glandular Trichomes and Polyphenol Oxidase Activity into an Advanced Solanum phureja-S. stenotomum Diploid Potato Population

Abstract: Preliminary data on the genetics of glandular trichomes and the feasibility of incorporating A and B glandular trichomes and polyphenol oxidase (PPO) activity from Solanum berthaultii Hawkes (Ber) into an advanced S. phureja Juz. et Buk.-S. stenotomum Juz. (Phu-Stn) diploid potato population are presented. A random sample of four Phu-Stn clones was intercrossed with a sample of three Ber progenies (pollen bulk per progeny)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(15 reference statements)
1
2
0
1
Order By: Relevance
“…The morphologies of the trichomes are similar to those described for other solanaceous plants, such as tomato (Luckwill, 1943), potato (Gibson, 1979;Gregory et al, 1986) and tobacco (Lin & Wagner, 1994). Datura wrightii is so far unique in that there are two discrete trichome phenotypes, whereas glandular trichome densities within other solanaceous species vary continuously among individuals (Lemke & Mutschler, 1984;Vallejo et al, 1994). Controlled crosses with both trichome phenotypes showed that in D. wrightii, trichome type is a monogenic trait.…”
Section: Introductionsupporting
confidence: 62%
“…The morphologies of the trichomes are similar to those described for other solanaceous plants, such as tomato (Luckwill, 1943), potato (Gibson, 1979;Gregory et al, 1986) and tobacco (Lin & Wagner, 1994). Datura wrightii is so far unique in that there are two discrete trichome phenotypes, whereas glandular trichome densities within other solanaceous species vary continuously among individuals (Lemke & Mutschler, 1984;Vallejo et al, 1994). Controlled crosses with both trichome phenotypes showed that in D. wrightii, trichome type is a monogenic trait.…”
Section: Introductionsupporting
confidence: 62%
“…Our results indicate that the inheritance of type B trichomes may be recessive, since these trichomes were not observed in any somatic hybrids. Alternatively, cytoplasmic DNA may affect the expression of type B trichomes, as suggested by Vallejo et al (1994b). Somatic hybrids presumably contain equal quantities of mitochondrial and chloroplast DNA from both parents, in contrast with sexual hybrids.…”
Section: Resultsmentioning
confidence: 99%
“…tatively inherited trait. A study by Vallejo et al (1994aVallejo et al ( , 1994b produced low heritability values for density of both types of trichomes and determined that additive genetic variance for trichome densities was low. Mehlenbacher et al (1983) were able to recover parental trichome densities in F 2 and backcross generations, indicating that these traits are controlled by relatively few genes.…”
mentioning
confidence: 99%
“…Le puceron rompt alors la tête d'un trichome de type A, ce qui a pour effet le relarguage de composés phénoliques (Avé et al, 1987). Ces produits entrent en contact avec des polyphénols oxydases et des péroxydases qui réagissent en un processus d'oxydation pour donner des quinones, formant un composé brun poisseux, collant, qui s'accumule sur le corps de l'insecte (Vallejo et al, 1994). Celui-ci est piégé, immobilisé, cesse de s'alimenter et meurt.…”
Section: Facteurs Physicochimiques De Surface Impliqués Dans L'acceptunclassified